Clinical case of endometrial cancer in a patient with complete doubling of the uterus and cervix - A. L. Chernyshova; L. A. Коlomiets; Yu. M. Truschuk (ABV-press, 2021)
A clinical case of endometrial cancer in a patient with complete doubling of the cervix and the body of the uterus is presented. The combination of this pathology is quite rare and is often accompanied by difficulties in timely diagnosis and choice of treatment tactics. The article presents an analysis of studies to identify similarities and differences in the clinical and morphological characteristics and prognosis of endometrial cancer associated with uterine abnormalities. This clinical case clearly demonstrates the features of the clinical course of endometrial cancer against the background of a congenital abnormality of the uterus. The standard combined treatment performed showed a good result and a satisfactory quality of life for the patient.